AS CONTRIBUIÇÕES DO PROGRAMA RESIDÊNCIA PEDAGÓGICA - SUBPROJETO BIOLOGIA DA UFDPar NA FORMAÇÃO DOS FORMADORES DE PROFESSORES DE CIÊNCIAS E BIOLOGIA - BRITO SANTOS, BRUNA (2025)
This dissertation presents a study focused on the training of teacher educators in Science and Biology within the scope of the Pedagogical Residency Program 3 Biology Subproject (PRPSB), linked to the undergraduate program in Biological Sciences at the Federal University of Delta do Parnaíba (UFDPar). The research emphasizes the central role of the PRP-SB9s regulatory documents in shaping critical and reflective pedagogical practices, aligned with contemporary social, political, and economic demands. The general objective is to analyze the contributions of the PRP-SB at UFDPar to the training of teacher educators in Science and Biology through an interpretative documentary analysis of the CAPES-issued PRP regulations, Institutional Projects (PI), and Biology Subprojects (SB) from all three editions of the program. The study adopts a qualitative, interpretive documentary approach. The corpus comprises the Portarias, Editais, PIs, and SBs related to the three PRP editions in the aforementioned course. The research seeks to answer the following central question: What are the contributions of the PRP-SB at UFDPar to the training of teacher educators in Science and Biology, based on the documents that guide the program9s actions and proposals? Although the normative documents reflect a pragmatic orientation4often reinforcing a separation between theory and practice4the role of teacher educators proves essential in reversing this trend. These educators foster spaces for socialization and reflection on teaching practices and strengthen the link between the university and the school, particularly through the work of supervising professors and preceptors. Nevertheless, there is a need to expand, within the normative framework, dedicated spaces for the professional development of teacher educators in order to overcome the divide between initial and continuing education. In this regard, selftraining emerges as a key strategy to enrich the activities carried out in the Professional Development Nucleus (NDP), the Pedagogical Residency Program Meetings (EPID), and other forums for reflection and exchange among educators. These processes contribute to teacher professionalization and the formation of collaborative networks. It is concluded that, despite the constraints imposed by official guidelines, the Institutional Projects and Subprojects offer meaningful pathways for addressing the challenges of articulating theory and practice and integrating initial and continuing teacher education.